2017
DOI: 10.1016/j.entcom.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Fun in Making: Understanding the experience of fun and learning through curriculum-based Making in the elementary school classroom

Abstract: In this article, we investigate the child's experience of fun and learning within curriculumintegrated Maker activities in the elementary school classroom. Little is currently understood as to how Making makes learning fun, particularly in formal educational contexts. We conducted an in-the-wild week-long study that implements Maker activities designed with 3 rd , 4 th , and 5 th grade teachers during science classes. Qualitative video-based analysis of the sessions for six students and analysis of all the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 26 publications
0
48
0
7
Order By: Relevance
“…Their analysis is, however, confined to assessing the overall level of emotional engagement, rather than analyzing and interpreting specific emotion indicators. Another study (Chu et al 2017) combined a questionnaire-based survey with video coding. Their in-depth qualitative video analysis focused on six students selected according to the preliminary results from the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their analysis is, however, confined to assessing the overall level of emotional engagement, rather than analyzing and interpreting specific emotion indicators. Another study (Chu et al 2017) combined a questionnaire-based survey with video coding. Their in-depth qualitative video analysis focused on six students selected according to the preliminary results from the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies (e.g., Apedoe et al 2008;Reynolds et al 2009;Bagiati et al 2010;Carroll et al 2010;Guo et al 2016;Lacy 2016;Guo et al 2017;Neve and Keith-Marsoun 2017;Zhang et al 2018Zhang et al , 2019 did mention DBL explicitly. While others (Chu et al 2017;Vongkulluksn et al 2018;Chan and Holbert 2019) mentioned makerspace and maker activities that suggest a specific type of DBL, emphasizing the essence of making in constructive learning. Four studies (Marks 2017;Tae 2017;Marks and Chase 2019;Phusavat et al 2019) explained that their cases include embedded design thinking in learning activities.…”
Section: Design-based Learningmentioning
confidence: 99%
“…Teachers were also encouraged to create fun and motivating environment for students to learn in elementary school. Chu, Angello, Saenz, & Quek, (2017) also reported that students best learning experience can be achieved by providing ITL.…”
Section: Discussionmentioning
confidence: 92%
“…While emphasizing the importance of game playing in learning, it was stated that games were among the most effective tools that make it entertaining and help children to learn with joy (Ara, 2009, p. 166). In fact, it was observed that technology-based learning that includes virtual media and digital games is a transformative approach to education beyond the incentives to develop teacher training (Chu, Angello, Saenz, & Quek, 2017). In the study by Duran and Kaplan (2014), where "comprehension with a word" game developed with mathematical concepts for mathematics course, it was determined that most students expressed positive views about the game and that they enjoyed the game.…”
Section: Discussionmentioning
confidence: 99%